2003
DOI: 10.1016/j.physletb.2003.08.070
|View full text |Cite
|
Sign up to set email alerts
|

Does the crossover from perturbative to nonperturbative physics in QCD become a phase transition at infinite N?

Abstract: We present numerical evidence that, in the planar limit, four-dimensional Euclidean Yang-Mills theory undergoes a phase transition on a finite symmetrical four-torus when the length of the sides l decreases to a critical value l c . For l > l c continuum reduction holds so that at leading order in N, there are no finite size effects in Wilson and Polyakov loops. This produces the exciting possibility of solving numerically for the meson sector of planar QCD at a cost substantially smaller than that of quenched… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(159 citation statements)
references
References 34 publications
8
151
0
Order By: Relevance
“…Using these estimates, we compared the scaled lattice data with p(s) for fixed f , b, N and V . One such comparison, at f = 0.15, b = 0.361653, L = 4, N = 44 and V = 7 4 with a gap of 0.1229 (4), is shown in Figure 1 and there is good agreement. In spite of the fact that data is needed over the entire range of s to get a good estimate of the skewness and kurtosis, we find agreement between lattice data and the universal estimates to within 5% for the skewness and to within 20% for the kurtosis for a wide range of gap values.…”
Section: The Determination Of F C (L)mentioning
confidence: 74%
See 1 more Smart Citation
“…Using these estimates, we compared the scaled lattice data with p(s) for fixed f , b, N and V . One such comparison, at f = 0.15, b = 0.361653, L = 4, N = 44 and V = 7 4 with a gap of 0.1229 (4), is shown in Figure 1 and there is good agreement. In spite of the fact that data is needed over the entire range of s to get a good estimate of the skewness and kurtosis, we find agreement between lattice data and the universal estimates to within 5% for the skewness and to within 20% for the kurtosis for a wide range of gap values.…”
Section: The Determination Of F C (L)mentioning
confidence: 74%
“…Recent lattice work has also indicated that specific non-local observables undergo large N phase transitions as they are dilated [3,4] and this happens while the Euclidean spacetime volume stays infinite in all directions. The critical scales are observable dependent; one can imagine associating with these observables an entire family of dilated images and somewhere along the dilation axis the large N transition takes place.…”
mentioning
confidence: 99%
“…For substantially smaller values of b the system is in a phase disconnected from continuum Yang-Mills theory. We also need to maintain b ≤ 0.369 to be sure that spontaneous Z 4 (N ) breaking at N = ∞ [15] is avoided on all our volumes, including our smallest, 12 4 . We mainly use the range of couplings 0.359 ≤ b ≤ 0.369.…”
Section: Parameter Choicesmentioning
confidence: 99%
“…One also finds that the deconfinement transition, which is first order for N ≥ 3, becomes sharper on smaller volumes as N increases suggesting [6] that here too one will have a phase transition on a finite volume at N = ∞. Indeed there appears to be a whole hierarchy of finite volume phase transitions at N = ∞ [7,2] which are, we shall argue below, related to the deconfinement transition.…”
Section: Introductionmentioning
confidence: 96%